Contribuições ao estudo de remediação de contaminantes de esgoto sanitário com o uso de lemnas - Albertin, Liliane Lazzari [UNESP] (My University, 2019)
Over the last seven years, our research group has investigated the wastewater polishing of Ilha Solteira with the use of duckweeds to improve the quality of the effluent to be released into the receiving body and to produce biomass with high added value. The research was based on the remediation of organic and emerging pollutants, such as pharmaceutical and personal care products. During this time, we found that the duckweed of the species Landoltia punctata had an excellent adaptation to our climatic conditions and to the wastewater to be treated, also revealing a high biomass production rate that, among other components, has large protein and starch contents, depending on the operating conditions of the treatment. The richness of this biomass makes it possible to be applied as a source of protein for animal feed or as a feedstock for ethanol production. In this way, it is possible to recover nutrients from the wastewater, potential polluters and eutrophication of water bodies, and to value a Wastewater Treatment Plant based on ecological and efficient processes, with low implantation and operation costs and low energy consumption. In this text, a systematized analysis will be presented on the various developments and questions that have arisen throughout the research. The theoretical background, the questions raised and the results obtained will be presented, trying to highlight the contribution in the field of science.

Ao longo dos últimos sete anos, nosso grupo de pesquisa investigou o polimento do esgoto sanitário de Ilha Solteira com o uso de lemnas, para melhoria da qualidade do efluente a ser lançado no corpo receptor e para produção de biomassa com grande valor agregado. As pesquisas basearam-se na remediação de poluentes orgânicos e emergentes, como produtos farmacêuticos e de cuidados pessoais. No decorrer desse tempo, constatamos que a lemna da espécie Landoltia punctata teve excelente adaptação para as nossas condições climatológicas e para o esgoto a ser tratado, revelando, ainda, possuir uma alta taxa de produção de uma biomassa que, dentre outros componentes, possui grandes teores de proteína e amido, dependendo das condições operacionais do tratametno. A riqueza dessa biomassa faz com que ela possa ser aplicada como fonte de proteína para ração animal ou como matéria-prima para geração de etanol. Dessa forma, é possível recuperar os nutrientes do esgoto, potenciais causadores de poluição e eutrofização de corpos hídricos, e valorizar uma Estação de Tratamento de Esgoto baseada em processos ecológicos e eficientes, com baixos custo de implantação e operação e baixo consumo de energia. Neste texto, será apresentada uma análise sistematizada sobre os vários desdobramentos e questionamentos que surgiram ao longo da pesquisa. Serão apresentados o embasamento teórico, as questões levantadas e os resultados obtidos, tentando evidenciar a contribuição no campo da ciência.
Contributions to the study of remediation of wastewater contaminants with the use of duckweeds
Keywords: Phytoremediation; Treatment with duckweeds; Wastewater treatment; Environmental sanitation; Fitorremediação; Tratamento com lemnas; Tratamento de esgoto sanitário; Saneamento ambiental